BUREAUCRATIC DISRUPTION AND THREATS OF UNEMPLOYMENT IN THE INDUSTRIAL REVOLUTION 4.0 ERA - Ristiandy, Risky (Journal of Local Government Issues (logos), 2020)
This article aims to analyze logical argument from the disruptive of information technology in Indonesian bureaucratic management. Technological advanced produces Artificial Intelligence (AI) which is an opportunity for the Government modernizes the bureaucracy. At same point, Disruption feared will make many Apparatus (ASN) lose their jobs. This article used literature study method by analyzing various articles in journals that discuss artificial intelligence, and the internet of things which are the subject of research. While, the literature about bureaucracy and public institutions which will be the research objectives. The result shows that the implementation AI has the potential of losing many bureaucratic positions and could impact on social upheaval if not managed effectively. In the future, many apparatus (ASNs) will be unemployed because public services have been replaced by artificial intelligence. Therefore, this is clearly a dilemma and challenge for government in the future to be modern governments with technological advanced. However, it still humanizes for public services and servants.